2018
DOI: 10.5539/jas.v10n5p34
|View full text |Cite
|
Sign up to set email alerts
|

Specific Management Areas as a Function of Dendrometric Properties of Eucalyptus and Physical-Chemical Attributes in an Oxisol

Abstract: Eucalyptus cultivation has expanded considerably in Brazil, especially in regions where soils have low fertility, as in the Brazilian Cerrado (Brazilian Savannah). In order to achieve high yield, it is necessary to know the appropriate time and place to perform the soil management, and to assist in this decision-making process, mathematical and computational models has been used and are a promising alternative. The objective of this study was to model the influence of plant and soil physical-chemical attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…There were high and positive correlations between the variables: RP1 x MRP; RP2 x MRP; RP3 x MRP, and RP4 x MRP. Studying the relationships with penetration resistance, Galindo et al, (2018) and Oliveira et al, (2019) also found high and positive correlations between the same variables. These variables also showed high negative correlations with garlic yield (GY).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…There were high and positive correlations between the variables: RP1 x MRP; RP2 x MRP; RP3 x MRP, and RP4 x MRP. Studying the relationships with penetration resistance, Galindo et al, (2018) and Oliveira et al, (2019) also found high and positive correlations between the same variables. These variables also showed high negative correlations with garlic yield (GY).…”
Section: Resultsmentioning
confidence: 89%
“…Garlic bulbs are rich sources of carbohydrates, proteins, phenols, and antioxidants. Annual global garlic production in 2015/16 was 27 million tons grown in approximately 1.5 million hectares in several countries under different climates (Faostat, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During a experiment with Eucalyptus camaldulensis, Galindo et al (2018) conducted a spatial variability analysis of dendrometric properties of eucalyptus and physical attributes of a Latosol and found average CV variabilities of 23.3 and 22.9%, respectively. In a similar study, Lima et al (2010) found average TH and DBH values ranging from 12 to 11.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Eucalyptus plant rapid growth and development is a possible explanation to this increase as well as the varied uses of timber and the easy adaption of the tree to different edaphoclimatic conditions. Even so, productivity of commercial eucalyptus farms in Brazil is still quite variable, averaging 60 m³ ha -1 , over seven-year rotations (Galindo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such an increase can be explained by eucalyptus rapid growth, wood use diversification, and adaptability to different edaphoclimatic conditions. However, the eucalyptus plantation yields in Brazil are still quite variable and may reach an average of 60 m³ ha-1 in a seven-year rotation (Galindo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%